Os jogos jurídicos: a influência das relações interpessoais na produção de verdade no campo jurídico e a legitimação da illusio na estrutura do direito como jogo - Pinheiro, Daniel Romero da Escóssia (2025)
The Law, despite being conceived as an objective and rational normative system, reveals in its practice a complex network of interactions, disputes, and strategies. This dissertation proposes an innovative approach to developing a new method for studying the legal field as a structured social game, in which legal agents act as players who mobilize symbolic resources to influence decisions and the structure of legal norms. The research employs a bibliographic review grounded in the theoretical framework of structuralist socio-anthropology, with a particular focus on the concepts formulated by Bourdieu, Elias, and Goffman, in conjunction with Huizinga’s analysis of social interactions as games. By applying the concept-method of Legal Games theorized in this study and analyzing the empirical research of Schritzmeyer, Lupetti Baptista, and Nuñez, the study investigates how the rules of the Legal Game are either contested or legitimized by agents possessing specific habitus and an accumulation of symbolic capital, internal or external to the legal field. The discussion explores how the influence of affections and symbolic exchanges in interpersonal relationships generates networks of interdependence within legal spaces, shaping the production of legal truth. To understand the legitimization of this truth-production process, Durand’s analysis of the legal imaginarium was employed as a tool to evaluate the symbols evoked as indicators of the accumulation of symbolic capital by individuals endowed with the habitus of juridical elites. The study concludes that the disparity in the accumulation of symbolic capital, resulting from the restricted access of certain agents to alliances and agreements — available only to those with certain shared habitus — has led to the emergence of a category of outsiders within the legal field. Ultimately, the research highlights that, beyond serving as a space for normative application, Law operates as a dynamic field of power, where strategies of self-preservation, reputation-building, and alliance formation play a central role. Thus, interpreting Law as a game provides a novel perspective on legal relations and opens new pathways for future investigations into the influence of social games in shaping the contemporary legal system.